Lab-on-a-chip using acoustic streaming for mixing and pumping fluids - Cardoso, V. F. (2011)
The research team is focused on lab-on-a-chip devices for clinical applications, with on-chip integration of electronic circuits, optical filters and (bio)sensors. An example of the work is a lab-on-a-chip where acoustic streaming technique is used to promote the mixing and the pumping of the fluids inside microchannels. The transducer that generates the acoustic streaming is based on a piezoelectric polymer, processed to be functionally graded for, in conjunction with the signal applied to the transducers, being able to control the movement and heating of the fluids. A highly selective optical interference filter cointegrated in CMOS allows the use of only a white light source when spectrophotometry is used as the detection technique, resulting in an actually portable device.